Exploring the flexibility of m-point quaternary approximating subdivision schemes with free parameter - Alhefthi, Reem K.; Ashraf, Pakeeza; Abid, Ayesha; Ghaffar, Abdul; Rezapour, Shahram; İnç, Mustafa (Amer Inst Mathematical Sciences-Aims, 2024)
In this study, we proposed a family of m-point quaternary approximating subdivision schemes, characterized by an explicit formula involving three parameters. One of these parameters served as a shape control parameter, allowing for flexible curve design, while the other two parameters identify different members of the family and determined the smoothness of the resulting limit curves. We conducted a thorough analysis of the proposed schemes, covering their smoothness properties, polynomial generation, and reproduction capabilities. Additionally, we examined the behavior of the Gibbs phenomenon within the family both theoretically and graphically, highlighting the advantages of the proposed schemes in eliminating undesirable oscillations. A comparative study with existing subdivision schemes demonstrated the effectiveness and versatility of our approach. The results indicated that the proposed family offered enhanced smoothness and control, making it suitable for a wide range of applications in computer graphics and geometric modeling.
Keywords: quaternary; subdivision scheme; shape control parameter; Laurent polynomial; Gibbs phenomenon